(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Renin synthesis and release is the rate-limiting step in the renin-angiotensin system, because cyclic adenosine monophosphate (cAMP) has been identified as dominant pathway for renin gene expression, and cAMP response element-binding protein (CREB) is found in the human and mouse renin promoter. This study aimed to evaluate the role of CREB in expression of the renin gene. Materials and Methods. We created conditional deletion of CREB in mice with low-sodium diet, specifically in renin cells of the kidney. To assess the effect of CREB on renin expression, immunostaining of renin was used in samples from wild-type mice and mice with gene knock-down of CREB. Cyclic AMP response element-binding-protein-binding protein (CBP) and p300 were measured in cultured renin cells of the mice, and RNA detection was done with real-time polymerase chain reaction. Results. With low-sodium diet, renin was expressed along the whole wall of the afferent glomerular arterioles in wild-type mice, while there was no increase or even decrease in renin expression in CREB-specific deletion mice; RNA level of renin in cultured cells decreased by 50% with single knock-down of CREB, CBP, or p300, and decreased 70% with triple knock-down of CREB, CBP, and p300. Conclusions. This study found that CREB was important for renin synthesis and the role of CREB can be achieved through the recruitment of co-activators CBP and p300.